1990
DOI: 10.1164/ajrccm/141.5_pt_1.1228
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients with Obstructive Sleep Apnea Have Thick Necks?

Abstract: During physical examination of patients with suspected obstructive sleep apnea (OSA), a comment is frequently made that they appear to have a short and fat neck. To confirm this subjective impression by objective measurements, we studied a group of 123 patients referred to us because of snoring and suspected OSA, all of whom had nocturnal polysomnography and measurements of external and internal neck circumference. The external neck circumference was measured at the level of the superior border of the cricothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
146
3
21

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(189 citation statements)
references
References 3 publications
19
146
3
21
Order By: Relevance
“…Accumulation of adipose tissue in the neck and enlarged neck have been proposed as possible causes of OSA in obese patients. 34 Neck circumference was a better predictor of RDI than waist circumference, and this result is apparently opposite to that reported by Grunstein et al in obese men. 26 However, it is notable that these authors investigated overweight and moderately obese patients, whereas we investigated severely obese patients; therefore, it is possible that waist circumference looses and neck circumference maintains its predictive power on sleep apnea in very fat men.…”
Section: Discussioncontrasting
confidence: 64%
“…Accumulation of adipose tissue in the neck and enlarged neck have been proposed as possible causes of OSA in obese patients. 34 Neck circumference was a better predictor of RDI than waist circumference, and this result is apparently opposite to that reported by Grunstein et al in obese men. 26 However, it is notable that these authors investigated overweight and moderately obese patients, whereas we investigated severely obese patients; therefore, it is possible that waist circumference looses and neck circumference maintains its predictive power on sleep apnea in very fat men.…”
Section: Discussioncontrasting
confidence: 64%
“…Similar increased fat deposition in the neck may explain why, in our sample, men had larger neck circumferences than women at similar BMIs. Such fat deposition has been associated with the development of SAHS [20][21][22]. It is noteworthy that the differences in neck circumference between the sexes were similar at all body masses and that it was not merely that obese men had larger necks while thin men and women had similar neck sizes.…”
Section: Discussionmentioning
confidence: 95%
“…[34][35][36][37] Katz et al 38 found that BMI, age and NC are significant predictors of OSAS. The incidence of OSAS peaks in the age group 50-60 years, but in individuals with a high BMI, this trend tends to peak in the age group 40-50.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact, however, that OSAS can affect individuals in any age group. 2,6,14,38 The presence of only one population sample profile, such as obesity, limits the study with respect to comparing anthropometric characteristics with the risk of developing OSAS. Nevertheless, we were able to detect that minimal variations in BMI, neck circumference, waist circumference, and waist-to-hip ratio may alter the risk of developing OSAS: the higher these values, the greater the risk of developing OSAS.…”
Section: Discussionmentioning
confidence: 99%